2017
DOI: 10.1111/jvh.12669
|View full text |Cite
|
Sign up to set email alerts
|

A systematic model improves hepatitis C virus birth cohort screening in hospital‐based primary care

Abstract: Despite national and local governing board recommendations in the United States of America to perform an HCV screening test in baby boomers, screening rates remain low. Our goal was to study the impact of an HCV screening and link-to-care programme with patient navigation in two New York City primary care practices. This was a 2-year prospective study of patients born between 1945-1965 ("baby boomers") with encounters at two primary care practices at the Mount Sinai Hospital between November 1, 2013 and Novemb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
31
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 70 publications
(74 reference statements)
6
31
1
Order By: Relevance
“…A lower HCV RNA positivity than expected was also observed in our cohort, with a proportion of 44% in the postimplementation/postcare coordination period compared with 75.9% and 84% in other studies [9, 12]. Those differences may also be explained in part by differences in the racial/ethnic makeup of the cohorts, as black or African American individuals have a lower rate of spontaneous HCV clearance compared with whites, which is partly explained by host genetic differences [17], and our cohort had a smaller proportion of black patients.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…A lower HCV RNA positivity than expected was also observed in our cohort, with a proportion of 44% in the postimplementation/postcare coordination period compared with 75.9% and 84% in other studies [9, 12]. Those differences may also be explained in part by differences in the racial/ethnic makeup of the cohorts, as black or African American individuals have a lower rate of spontaneous HCV clearance compared with whites, which is partly explained by host genetic differences [17], and our cohort had a smaller proportion of black patients.…”
Section: Discussionsupporting
confidence: 72%
“…Jonas et al [9] described a prevalence of 3.25% in a Kaiser Permanente cohort from Maryland, Virginia, and the District of Columbia, and Goel et al [12] described a prevalence of 3.3% in a New York City university-based primary care cohort of persons born between 1945 and 1965; both groups showed a greater proportion of black and Hispanic patients. A review of HCV seroprevalence in state prisons showed a wide range of seroprevalence from 7.5% to 41.2% between states, and the prevalence among Hispanic subpopulations also varies by Hispanic/Latino background and city, with the highest prevalence described in the Bronx and lower prevalence in Chicago, Miami, and San Diego [3, 13].…”
Section: Discussionmentioning
confidence: 99%
“…Data examining subsequent linkage to care and curative treatment from other similar EHR‐based interventions for HCV screening of baby boomers in primary care are limited. Our rates of visits with HCV specialists and initiation on DAA therapy were higher than those of other studies: 77% newly diagnosed patients seen by specialists in the study by Goel et al and 21% and 57% of newly diagnosed patients started on DAA in the studies by Mera et al and Miller et al, respectively . While most of the newly diagnosed patients had early‐stage disease, 20.7% had evidence of either cirrhosis or advanced fibrosis at the time of initial referral.…”
Section: Discussioncontrasting
confidence: 60%
“…Despite this evidence‐based recommendation, uptake of one‐time universal HCV screening among baby boomers remains low. The reported ranges for screening among this cohort vary but in general are estimated to be <30%, even after implementing interventions specifically aimed at increasing HCV screening among baby boomers . Various approaches have been evaluated to optimize screening rates including integration of HCV screening into other preventive health screening like colonoscopy or human immunodeficiency virus testing, as well as screening in emergency room and inpatient settings .…”
mentioning
confidence: 99%
“…It should be noted that our centre did not initiate a specific training programme, making the implementation of this approach very simple. Brady et al compared, in 3 medical systems, the effect of a mailed patient reminder, an EMR‐based alert and direct patient solicitation at the time of a visit, and found all 3 approaches to increase testing dramatically over baseline . Further investigation of the utility of such strategies, along with systems that improve testing workflow in primary care settings, is needed.…”
Section: Discussionmentioning
confidence: 99%